1990
DOI: 10.1289/ehp.89-1567774
|View full text |Cite
|
Sign up to set email alerts
|

Degradation pathways of PCB upon gamma irradiation.

Abstract: In order to understand the modifications of the chromatographic profile of Aroclor 1260 upon gamma irradiation, a total of 14 pure polychlorinated biphenyl (PCB) congeners were separately irradiated in solution. Dechlorination was observed, and the generated products were investigated by gas chromatography and mass spectrometry. Degradation proceeds more rapidly in methanol/water mixture than in petroleum ether, but the relative amount of ortho-dechlorinated congeners formed upon irradiation was smaller in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The reactivity of chlorines at various positions was weakened in the order as ortho-position > meta-position > para-position. [33,34] Dechlorination of PCB77 in aqueous solution by the hybrid system was in agreement with previous reports that the ortho-chlorines were lost preferentially when other positions were substituted by chlorines.…”
Section: Dechlorination Mechanism Proposed For Pcb77 Degradationsupporting
confidence: 92%
“…The reactivity of chlorines at various positions was weakened in the order as ortho-position > meta-position > para-position. [33,34] Dechlorination of PCB77 in aqueous solution by the hybrid system was in agreement with previous reports that the ortho-chlorines were lost preferentially when other positions were substituted by chlorines.…”
Section: Dechlorination Mechanism Proposed For Pcb77 Degradationsupporting
confidence: 92%
“…It may be suggested that in general the reactivities of the chlorines at various positions of phenyl rings decrease in the order: ortho > meta > para, which is not in good agreement with the result of PCBs degradations upon gamma irradiation. The reactivity of chlorines at various positions upon gamma irradiation decrease in the order: ortho > para > meta [18]. In our experiments, paradechlorinations are also observed, and such a degradation pathway is barely observed upon UV irradiation of PCB containing other chlorine substituents in addition to para chlorine atoms [25].…”
Section: Resultsmentioning
confidence: 82%
“…These results showed that considerable modifications of the PCB's profile occurred at this radiation dose and that the modifications are generally greater in polar solvents than in nonpolar ones. The degradation pathways of some pure model PCB congeners were investigated in aliphatic and methanolic solvents to explain these results (Lépine and Massé, 1990b).…”
Section: Mechanisms and Parameters Involved In Radiation-induced Degr...mentioning
confidence: 99%